2016
DOI: 10.1111/ijau.12083
|View full text |Cite
|
Sign up to set email alerts
|

An International Perspective on Audit Report Lag: A Synthesis of the Literature and Opportunities for Future Research

Abstract: Audit report lag (ARL) is the length of time from a company's fiscal year-end to the audit report date, and is often viewed as the most important financial reporting timeliness determinant. Given that timeliness is an area of interest to investors, managers, regulators, auditors and academics, an understanding of ARL determinants is extremely important. As financial markets become more globally oriented, an international understanding of ARL determinants becomes even more important. This paper summarizes the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
89
0
7

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 83 publications
6
89
0
7
Order By: Relevance
“…A recent paper by Abernathy, Barnes, Stefaniak, and Weisbarth () has provided a first comprehensive review on the determinants of ARL in an international setting. Abernathy et al () concluded from their review that “the ARL literature as it relates to audit characteristics provides evidence that companies audited by Big N auditors and industry specialist auditors have shorter ARL.” Yet our meta‐analysis reports that about 53% of the published results provide insignificant coefficients on the Big 4 variable, despite the compelling theoretical arguments that Big 4 auditing reduces ARL. The same holds for the “busy season” variable, where 54% of the studies report insignificant coefficients whilst 16% of the studies report a coefficient that is contrary to the expected positive sign.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper by Abernathy, Barnes, Stefaniak, and Weisbarth () has provided a first comprehensive review on the determinants of ARL in an international setting. Abernathy et al () concluded from their review that “the ARL literature as it relates to audit characteristics provides evidence that companies audited by Big N auditors and industry specialist auditors have shorter ARL.” Yet our meta‐analysis reports that about 53% of the published results provide insignificant coefficients on the Big 4 variable, despite the compelling theoretical arguments that Big 4 auditing reduces ARL. The same holds for the “busy season” variable, where 54% of the studies report insignificant coefficients whilst 16% of the studies report a coefficient that is contrary to the expected positive sign.…”
Section: Introductionmentioning
confidence: 99%
“…The annual audit length has been specified as one of the most significant factors determining the timeliness of financial reporting by companies (Knechel & Sharma, 2012;Abernathy, Barnes, Stefaniak & Weisbarth, 2017). As required by regulations in several countries, companies are only allowed to issue their financial reporting after certification of external auditor and release the audit report (Abernathy et al, 2017). Audit lag is identified as the number of days from the end of company's fiscal year to the date of audit report (Swanson & Zhang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of audit lag to investors, identifying the determinants of audit lag has been of interest of scholars as exhibited in recent research conducted by Abernathy et al (2017), Sharma, Tanyi and Litt (2017), Wan-Hussin, Bamahros and Shukeri (2018) and Salehi, Bayaz and Naemi (2018). However, very few empirical studies investigated the factors impacting the lag of audit report in the MEC particularly with factors of corporate governance (see for example Afify, 2009;Baatwah et al, 2015a;Basuony et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While prior research has investigated a number of firm-, economic-, and auditor-specific characteristics associated with financial reporting timeliness (e.g., Abernathy, Barnes, Stefaniak, & Weisbarth, 2016;Bamber, Bamber, & Schoderbek, 1993;Knechel & Payne, 2001;Sengupta, 2004), research has yet to investigate the association between management characteristics (particularly human capital attributes) and financial reporting timeliness. This lack of evidence is surprising given the influence that managers have on the financial reporting and audit process, particularly subsequent to the passage of the Sarbanes-Oxley Act (Sarbanes-Oxley Act, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…8. Audit Risks in Certain Emerging Markets: http://pcaobus.org/ standards/qanda/2011-10-03_apa_8.pdf.2 For example,Michaely, Rubin, and Vedrashko (2014) note that the decision to announce earnings is made by the CEO and CFO after consultation with the audit committee and/or general counsel.3 SeeAbernathy et al (2016) for a review of the ARL literature.4 We thank Peter Demerjian for making his data available on his faculty website: http://faculty.washington.edu/pdemerj/data.html.5 In the Audit Analytics database, the variable HISTORICAL_IS_ ACCELERATED_FILER (HISTORICAL_IS_LARGE_ACCELERATED_FILER) indicates how the registrant identified their accelerated filer (large filer status) status.6 To reduce the influence of outliers, we winsorize the following variables at the 1st and 99th percentiles: LEVERAGE,ROE, DISACC, and AUDITFEES. 7 To increase variation in the dependent variable, we use raw EAL and ARL measured in number of days (as opposed to the log transformation).…”
mentioning
confidence: 99%